Changes in glucose metabolism among recipients with diabetes 1 year after kidney transplant: a multicenter 1-year prospective study - Bang, Jun Bae; Oh, Chang-Kwon; Kim, Yu Seun; Kim, Sung Hoon; Yu, Hee Chul; Kim, Chan-Duck; Ju, Man Ki; So, Byung Jun; Lee, Sang Ho; Han, Sang Youb; Jung, Cheol Woong; Kim, Joong Kyung; et al. (Frontiers in Endocrinology, 2023)
Background Diabetes mellitus is a common and crucial metabolic complication in kidney transplantation. It is necessary to analyze the course of glucose metabolism in patients who already have diabetes after receiving a transplant. In this study, we investigated the changes in glucose metabolism after transplantation, and a detailed analysis was performed on some patients whose glycemic status improved. Methods The multicenter prospective cohort study was conducted between 1 April 2016 and 31 September 2018. Adult patients (aged 20 to 65 years) who received kidney allografts from living or deceased donors were included. Seventy-four subjects with pre-transplant diabetes were followed up for 1 year after kidney transplantation. Diabetes remission was defined as the results of the oral glucose tolerance test performed one year after transplantation and the presence or absence of diabetes medications. After 1-year post-transplant, 74 recipients were divided into the persistent diabetes group (n = 58) and the remission group (n = 16). Multivariable logistic regression was performed to identify clinical factors associated with diabetes remission. Results Of 74 recipients, 16 (21.6%) showed diabetes remission after 1-year post-transplant. The homeostatic model assessment for insulin resistance numerically increased in both groups throughout the first year after transplantation and significantly increased in the persistent diabetes group. The insulinogenic index (IGI30) value significantly increased only in the remission group, and the IGI30 value remained low in the persistent diabetes group. In univariate analysis, younger age, newly diagnosed diabetes before transplantation, low baseline hemoglobin A1c, and high baseline IGI30 were significantly associated with remission of diabetes. After multivariate analysis, only newly diagnosed diabetes before transplantation and IGI30 at baseline were associated with remission of diabetes (34.00 [1.192–969.84], P = 0.039, and 17.625 [1.412–220.001], P = 0.026, respectively). Conclusion In conclusion, some kidney recipients with pre-transplant diabetes have diabetes remission 1 year after transplantation. Our prospective study revealed that preserved insulin secretory function and newly diagnosed diabetes at the time of kidney transplantation were favorable factors for which glucose metabolism did not worsen or improve 1 year after kidney transplantation.